Drying of lucuma (Pouteria obovata) using the technique of Refracting WindowTM - Gamboa, Diego (2014)
Lucuma is a fruit that is experiencing a growing trend in commercial ground into flour for use in the food industry. This study aimed to obtain lucuma flour using the method of refractive window drying and evaluate the effect of the thickness of lucuma pulp and drying time on flour moisture and color. It was used a Composite Design Central Rotary (DCCR) with time between 10 and 50 min and the thickness between 1 and 3 mm. A fixed temperature of 95 °C and mylar film (metallized polyethylene terephthalate) as a refractory film of 0.1 mm was used. It was determined that the optimal conditions for lucuma flour (9.8% moisture) with this technique is when the thickness was 1.3 mm and with a time of 15 minutes; in these conditions, the effective diffusivity of water is 2.53 E-7 m2/s.